100 Years after the Spanish Flu Pandemic. The Evolution of the Influenza Virus and the Development of the Flu Vaccine - N. I. Briko (Эпидемиология и вакцинопрофилактика)
The report includes a historical panorama of flu epidemics and pandemic from Hippocrates to the present day. An in-depth analysis of the pandemics and epidemics of the 20th and 21st centuries is given. The characteristics of the influenza virus, its epidemiology and the system of infection surveillance are presented. In the historical, scientific and practical aspects, relevancy for specific prevention of influenza has been considered.